1997
DOI: 10.1046/j.1365-2249.1997.4831379.x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic sinusitis refractory to standard management in patients with humoral immunodeficiencies

Abstract: SUMMARYChronic refractory sinusitis is a common feature in patients with primary immunodeficiencies. The efficacy of standard therapeutic strategies is questionable. In an open trial we evaluated the efficacy of azithromycin, N-acetylcysteine and topical intranasal beclomethasone (100 mg twice daily for 6 weeks) in 16 patients with primary immunodeficiencies (median age 13 . 5 years, range 5-32 years). All patients suffered from chronic sinusitis despite regular immunoglobulin replacement therapy every 3 weeks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0
13

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 19 publications
(22 reference statements)
0
37
0
13
Order By: Relevance
“…The most frequent PID associated with sinusitis is humoral immunodeficiency. This disorder includes selective IgA deficiency (SIgAD), common variable immunodeficiency (CVID), and specific antibody deficiency (SAD), which is characterized by normal IgG levels but an impaired response to polysaccharide vaccines [17][18][19][20][21]. One study reported considerable differences in the incidence of sinusitis in PIDs, such as agammaglobulinemia (11.52%), CVID (9.4%), SAD (1.8%), IgG subclass deficiency (13.41%), SIgAD (6.58%), and hyper-IgM syndrome (0.7%) [19].…”
Section: Sinusitismentioning
confidence: 99%
See 1 more Smart Citation
“…The most frequent PID associated with sinusitis is humoral immunodeficiency. This disorder includes selective IgA deficiency (SIgAD), common variable immunodeficiency (CVID), and specific antibody deficiency (SAD), which is characterized by normal IgG levels but an impaired response to polysaccharide vaccines [17][18][19][20][21]. One study reported considerable differences in the incidence of sinusitis in PIDs, such as agammaglobulinemia (11.52%), CVID (9.4%), SAD (1.8%), IgG subclass deficiency (13.41%), SIgAD (6.58%), and hyper-IgM syndrome (0.7%) [19].…”
Section: Sinusitismentioning
confidence: 99%
“…Only a few studies have investigated the treatment of chronic sinusitis in patients with PIDs, although it seems that treatment involves both medical and surgical approaches, as occurs in immunocompetent individuals. In general, broad-spectrum antibiotics, saline nasal washes, anti-inflammatory agents, and immunoglobulin replacement therapy could reduce the frequency and severity of sinusitis in PID patients [18,25]. While the role of sinus surgery has not been well defined, it seems that PID patients experience similar benefits to immunocompetent populations in terms of symptoms and quality of life [26][27][28][29].…”
Section: Sinusitismentioning
confidence: 99%
“…The occurrence of a dermatomyositis-like syn-VOL. 22,2009 PRIMARY ANTIBODY DEFICIENCIES 401 drome, marked by peripheral edema, erythematous rash, and evidence of inflammation of the skin and muscle on biopsy specimens, has been associated with disseminated enteroviral disease in patients with XLA (84) (see below). At the time of diagnosis, most, but not all, patients have low serum immunoglobulin levels, with IgG levels of Ͻ200 mg/dl, IgA levels of Ͻ15 mg/dl, and IgM levels of Ͻ40 mg/dl (141).…”
Section: Primary Antibody Deficiencies Agammaglobulinemiasmentioning
confidence: 99%
“…22,2009 PRIMARY ANTIBODY DEFICIENCIES 405 (93). This is a result of an additional profound impairment of cellular immunity associated with these disorders, which are therefore better classified as combined immunodeficiencies.…”
Section: Infections and Primary Antibody Deficienciesmentioning
confidence: 99%
See 1 more Smart Citation